KEMISKINAN DAN KETAHANAN PANGAN DI INDONESIA: TANTANGAN URBANISASI DAN PELUANG DIVERSIFIKASI PANGAN - Jumhar Daulay; Nermelita Kaloko; Reni Ria Armayani Hasibuan; Siska Kumala Sari (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The increasing urbanization in Indonesia has a significant impact on poverty and food security, especially in urban areas. The migration of people from rural areas to cities is not always followed by an increase in welfare due to limited formal employment opportunities, so many migrants work in the informal sector with low and unstable incomes. This condition increases the risk of urban poverty and weakens households’ ability to meet adequate and nutritious food needs. This study aims to analyze the relationship between urbanization, poverty, and food security in Indonesia and to examine the opportunities for food diversification as a strategy to strengthen urban food security. The research method used is a qualitative method with a descriptive approach. Data were obtained through literature studies, policy document analysis, and a review of previous research results relevant to the themes of poverty, urbanization, and food security. Data analysis techniques were carried out through data reduction, data presentation, and interpretive conclusions. The results of the study show that poverty is a major factor causing household food insecurity in urban areas, while food diversification through the use of local resources, urban agriculture, and agricultural technology innovations has the potential to strengthen food security in a sustainable manner.